152k views
5 votes
Perform the indicated operation to write given polynomial in standard form: (2x^3 − 6x^2 − 7x − 2) +(x^3 +x^2 +6x − 12)

User RBusarow
by
5.9k points

1 Answer

0 votes

Answer:


\left(2x^3-6x^2-7x-2\right)+\left(x^3+x^2+6x-12\right)=3x^3-5x^2-x-14

Explanation:

To add the polynomials

Remove parentheses:


\left(2x^3-6x^2-7x-2\right)+\left(x^3+x^2+6x-12\right)=2x^3-6x^2-7x-2+x^3+x^2+6x-12

Group like terms:


=2x^3+x^3-6x^2+x^2-7x+6x-2-12

Add similar elements:


=3x^3-6x^2+x^2-7x+6x-2-12\\=3x^3-5x^2-7x+6x-2-12\\=3x^3-5x^2-x-2-12\\=3x^3-5x^2-x-14

The Standard Form for writing down a polynomial is to put the terms with the highest degree first,its term of 2nd highest is 2nd etc..

In our case the standard form is


\left(2x^3-6x^2-7x-2\right)+\left(x^3+x^2+6x-12\right)=3x^3-5x^2-x-14

User Ramashankar
by
5.7k points